Meta-Analysis of the Effects of Different Farming Measures on Greenhouse Gas Emissions from Farmland in China - Siya Wang; Xinyu Wei; Xiaobo Luan; Jiabei Li; Yuxin Yang; Jie Pang; Fei Gao (Land)
Reducing greenhouse gas (GHG) emissions from agricultural fields is crucial for mitigating climate change and promoting sustainable agriculture. This study conducted a meta-analysis of 82 domestic experimental studies to assess the effects of fertilization, tillage, and straw return on CH4, CO2, and N2O emissions across different regions in China. The key findings include: fertilization measures: split fertilization increased CH4 and N2O emissions, whereas a single application had the strongest impact on CO2 emissions. The application of carbon alone or in combination with NPK reduced GHG emissions, while the combination of nitrogen and farmyard manure significantly increased CH4 and CO2 emissions. Tillage measures: tillage generally reduced CH4 and CO2 emissions but increased N2O emissions. No-tillage effectively suppressed CH4 emissions, while rotary tillage significantly reduced CO2 emissions. Straw return: straw returning through rotary tillage led to the highest increase in CH4 and CO2 emissions, whereas direct straw return most notably enhanced N2O emissions. This study provides insights into optimizing agricultural practices to mitigate GHG emissions and offers guidance for sustainable and low-carbon agricultural development.